Electrostatic converter with an electret-like elastomer membrane for large scale energy harvesting of low density energy sources. (September 2015) - Peter, D.; Pichler, R.; Bauer, S.; Schwödiauer, R.
Abstract: Low density energy sources, like wind and solar energy, are widely available and they are increasingly used for electricity conversion worldwide. Ambient energy sources with even lower energy densities are universally available and could equally be converted into electricity with large scale special purpose converter systems. This work discusses a simple concept for an electret-based electrostatic converter suitable for large scale conversion of ambient low density energy sources. The converter is a capacitive charge pump capable of working at low frequencies ( ≤ 1 Hz ) with a very low mechanical input energy and a high conversion efficiency. With a charged electret-like elastomer membrane the converter can operate without an initial bias voltage supply. First tests with a simple proof-of-concept demonstrator resulted in a mechanical input energy of 332 μJ (9.1 μJ/cm 2 ) and a converted electrical output energy of 206 μJ (5.7 μJ/cm 2 ) per conversion cycle. This gives a total conversion efficiency of 63%. Graphical abstract: